(untitled) (Bangladesh Critical Care Journal, 2021)
There are diagnostic and therapeutic challenges in cases of symptomatic gall bladder disease in patients with situs inversus totalis (SIT), where there is complete reversal of visceral topography in thorax, abdomen or both. The difficulty to treat these patients with conventional laparoscopic cholecystectomy may be more pronounced for right handed surgeon and requires modifications in working ports and their positions. We present a case of laparoscopic cholecystectomy in a patient with SIT, and describe the technical details that enable the safe conclusion of the operation. Bangladesh Crit Care J March 2021; 9(1): 43-45